Efektifitas Pendidikan Kesehatan Dengan Media Booklet Terhadap Peningkatan Partisipasi Masyarakat Pada Bank Sampah Di Kabupaten Badung - Suyasa, I Nyoman Gede; Sudarmanto, I Gede; Purna, I Nyoman (Jurnal Kesehatan Lingkungan (JKL), 2023)
Waste dumps are affected by overcrowding and human activity. Badung Regency produces 250 tons of garbage per day, to handle the waste problem Badung District Government is one of its efforts to establish a waste bank. This garbage bank was formed in the neighborhood of banjar, villages, schools and private institutions. The purpose of the study was to find out the increase in community participation in the waste bank program before and after health education with the media booklet. This type of research is pre-experimental research with one group pre-test-post-test design. The study population is the head of the family in Badung Regency. The sample size calculation obtained a sample of 337 people. Sampling with cluster random sampling, data collected using a questionnaire. Data collection before treatment and one month after treatment. Data analysis with paired t-test statistics. The results obtained by the level of community participation in waste banks before health education with the media booklet is very less 106 people (31.45%), less 14 people (4.15%), 40 people enough (11.87%), both 105 people ( 31.16%) and very good 72 people (21.36%). The level of community participation in the waste bank after health education with the media booklet is 31 people (9.20%), 175 people (51.93%) and very good 131 people (38.87%). And there are differences in community participation in waste banks before and after health education with a media booklet with a significance of 0,000. It is expected that the management of the official waste bank related to socialize the waste bank program to the public with the media booklet, facilitate prices to be stable and prepare transportation and personnel to take garbage to the homes of residents.